Застосування інтерактивних форм навчання при викладанні інженерної дисципліни - Михайленко, Олена Юріївна; Михайленко, Елена Юрьевна; Mykhailenko, Olena; Чаплінський, Андрій Петрович; Чаплинский, Андрей Петрович; Chaplinskyi, Andrii; Дмітрієв, Юрій Олексійович; Дмитриев, Юрий Алексеевич; Dmitriiev, Yurii (ТДАТУ, 2021)
UK : У статті описаний досвід практичної реалізації універсальних інтерактивних форм навчання, використовуваних в процесі викладання інженерної дисципліни. Представлені інтерактивні форми навчання дозволяють активізувати навчально-пізнавальну роботу студентів. EN : Experience in the practical implementation of universal interactive forms of learning used in the teaching of engineering discipline is described in the article. Interactive forms of learning that allow to intensify the educational and cognitive studying of students are presented.
Using of interactive forms of learning in teaching engineering discipline
Keywords: інтерактивні форми навчання; ефективність процесу навчання; навчально-пізнавальна робота; ефективність навчально-виховного процесу; interactive forms of learning; efficiency of the learning process; educational and cognitive studying; efficiency of the educational process